IMPLEMENTASI PROJEK PROFIL PELAJAR PANCASILA DALAM MENINGKATKAN KREATIFITAS SISWA BERBASIS KURIKULUM MERDEKA DI SEKOLAH DASAR - Laili, Nur; Setiaputri, Alvina Nanda; Rahmayanti, Jesica Dwi; Nadlir, Nadlir (Universitas Islam Darul 'Ulum Lamongan, 2024)
Implementation of the Pancasila student profile is able to strengthen personality and develop skills, take responsibility and train problem-solving abilities and deal with problems in the environment. The aim of this research is to describe the implementation of the project to strengthen the profile of Pancasila Students in the independent curriculum and analyze the creative dimensions at the Muhammadiyah 16 Surabaya elementary school. This research uses qualitative methods and data analysis is descriptive. Data collection techniques are observation, interviews and documentation. The results of this research show that the implementation of the Pancasila student profile project to increase student creativity based on the independent curriculum in elementary schools is based on the Pancasila student profile with the dimensions of Faith and Devotion to God as well as Noble Character, Global Diversity, Mutual Cooperation, Independence, Critical Reasoning and Creativity through activities intracurricular, co-curricular and extracurricular learning which aims to build the character of students. The implementation of the Pancasila student profile project in increasing student creativity based on the independent curriculum at SD Muhammadiyah 16 Surabaya is carried out through various activities and implemented in various school activity programs to provide a positive impact on student growth.